The Relationship between Psychological Status (Depression and Anxiety) and Social Support and Sexual Function - Saberi, Nayereh; Amir Ali Akbari, Sedigheh; Mahmoodi, Zohreh; Nasiri, Malihe (Advances in Nursing & Midwifery, 2017)
Abstract Introduction: Given that large numbers of marital problems arise from lack of proper satisfaction with sexual desire (libido) as well as lack of awareness towards the complicated dimensions of this fundamental motive, the purpose of the present study was to determine correlations between psychological state (depression and anxiety), social support, and sexual function among females of the reproductive age. Methods: This study was a descriptive-analytic research on 400 females referred to clinics affiliated with Shahid Beheshti University of Medical Sciences in the city of Tehran, during year 2015. The study sample was recruited by cluster and multi-stage random sampling method. The Sexual Function Questionnaire, Demographic Questionnaire, Scale of Perceived Social Support, Spielberger’s Anxiety Inventory, and Beck Depression Inventory were also used to collect the data. The obtained data was analyzed through the SPSS software via descriptive statistics, t test, one way Analysis of Variance (ANOVA), as well as chi-square test. Results: The findings revealed that 4.5% of females had poor level of sexual functioning. In addition, 24.5% of females benefited from low social support and also 75% and 9% of the given individuals had chronic depression and severe anxiety, respectively. According to the results of this study, sexual functioning was correlated with female’s age, husband’s age, age of first pregnancy, length of marriage, duration of having private rooms, and history of infertility (P ˂ 0.05). Furthermore, there were relationships between sexual functioning and depression as well as anxiety and social support (P ˂ 0.05). Conclusions: It was concluded that sexual functioning was correlated with psychological state (depression and anxiety) and social support. Thus, it was recommended to conduct screening tests in terms of the variables examined.